1998
DOI: 10.1080/15216549800203212
|View full text |Cite
|
Sign up to set email alerts
|

Removal of polyphenolic compounds from aqueous plant extracts using polyamide minicolumns

Abstract: SummaryAn improved method for the removal of polyphenolic compounds from aqueous extracts of plants is presented, The method removes >99% polyphenolic compounds from 5rag of extract. The method is simple, robust and reproducible. We examined the removal of polyphenolics from 5 different aqueous extracts of Chinese medicinal herbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 6 publications
0
32
0
1
Order By: Relevance
“…1). It is known that simple phenolic compounds with fewer phenolic hydroxyl groups bind less strongly to the polyamide resin, and can be eluted from the column (Collins et al, 1998). Therefore, it is speculated that there were still some tannins, such as gallic acid, present in the P. clypearia extract after treatment with the polyamide column as reported previously by Chen (1994).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…1). It is known that simple phenolic compounds with fewer phenolic hydroxyl groups bind less strongly to the polyamide resin, and can be eluted from the column (Collins et al, 1998). Therefore, it is speculated that there were still some tannins, such as gallic acid, present in the P. clypearia extract after treatment with the polyamide column as reported previously by Chen (1994).…”
Section: Resultsmentioning
confidence: 86%
“…1). In order to determine the influence of the tannins on the effect of the anti-HSV-1 activity of the herbs, these extracts were treated with a small polyamide column chromatography to remove them (Collins et al, 1998). It was found that the anti-HSV-1 activity of the aqueous extracts treated with the polyamide column was diminished dramatically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly common highly apolar compounds, such as fatty acids (Balunas et al, 2006), common polar compounds, such as polyphenols and flavonoids (Zhu et al, 1997(Zhu et al, , 2013Zou et al, 2002), as well as chlorophyll (Henrich et al, 2006) might be especially problematic since they can interfere with a range of different assays. Much effort is necessary to remove such constituents from samples prior to testing (Cardellina et al, 1993;Collins et al, 1998;Picker et al, 2014) or to modify the assay system in order to avoid their detection (Sasiela et al, 2008). Next to organic molecules, also some inorganic constituents, such as metals, can lead to false positive results in HTS (Hermann et al, 2013).…”
Section: Challenges Contributing To the Decline Of Plant-derived Natumentioning
confidence: 99%
“…The column bound polyphenolic compounds were released by elution with 100 ml of absolute methanol (Collins, 1998).…”
Section: Organic Solvents and Column Partitioning Of Crude Extractsmentioning
confidence: 99%